Comparison between impacted maxillary and mandibular canines in an Iraqi population: prevalence and classification - Abbas Alhussaini, Ali Hussien; Al-Ghurabi, Zainab Hassan; Sabri Yas, Layla; Abdul Jabbar Abdul Qader, Omar; Ahmad Rajion, Zainul (Al-Rafidain University College, 2025)
Background: Concerning the importance of impacted canines for aesthetics and function to improve patients’ health, it is crucial to provide the oral surgeon and orthodontist with a complete analysis of their location, angulation, and relation with adjacent teeth. Objective: To determine and compare the frequencies of different types of impacted maxillary and mandibular canines under the current classification systems in an Iraqi population sample. Methods: This study retrospectively examined the cone beam computed tomography scans of 1000 Iraqi patients aged 12–40 years (380 males and 620 females) who had attended the Oral and Maxillofacial Radiology Department at Ghazi Al-Hariri and Al-Sadder City Hospitals. Results: Of the 1000 patients, 49 had impacted maxillary canines (4.9%), of which 18(36.7%) were male and 31(63.3%) were female. Bilateral impaction was more common than unilateral impaction (61.2% vs. 19.0%). Type II was the most common impaction type. In addition, 20 patients had impacted mandibular canines (2%), of which 8(40.0%) were male and 12(60.0%) were female. Bilateral impaction was less common than unilateral impaction (25.0% vs. 75.0%). Type III was the most common impaction. Conclusions: Impaction was more common for maxillary canines (4.9%) than for mandibular canines (2.0%). Type II impaction was the most common for maxillary canines, followed by Types I, IV, and VII. In contrast, Type III impaction was the most common for mandibular canines, followed by Type V